The Contestation of Magic in the Adaptation of a Fairy Tale into a Film: Snow White to Snow White and the Huntsman - Pujiati, Hat; Faruk, Faruk; Salam, Aprinus (Universitas Negeri Semarang, 2023)
Fairy tales are considered stories for children because of magical events in them. The consideration is based on assumptions that children's rationality is not well-developed yet. However, adaptation of fairy tales continues in the time when people do not believe in magic anymore, even they multiply the magical elements in the works of adaptation. This article analyses positions of magical and real elements in a fairy tale entitled ‘Snow White’ by Brothers Grimm and a film directed by Rupert Sanders called Snow White and the Huntsman. We apply theory of Adaptation by Linda Hutcheon to recognize the adaptation as a product, process, and context while to map the magical elements in the two stories we apply magical realism by Wendy B. Faris. To explore the context of adaptation of the magical elements, constructionism by Vivien Burr is also applied. The results of this paper analysis show the position of magical element in the adaptation varies. The variation become possible First, the magical element is dominant in Snow White by Grimm but logic invades the magical element. Second, the adaptation of Snow white in the form of film shows the dominance of magical element in a hyper-contestation of magic. Third, both works are not magical realism works which support the same agenda in different ways. Grimm’s version supports colonialization discourse with the logic of the post-enlightenment paradigm, and the film version supports re-colonialization discourse through the contestation of magic that is technological rather than ideological.